Perkembangan Teknologi Artefak Serpih Batu Pada Paruh Awal Holosen di Leang Batti, Sulawesi Selatan - nfn Suryatman; nfn Fakhri; Ratno Sardi; Budianto Hakim (Berkala Arkeologi, 2020)
Intensive research in prehistoric caves in South Sulawesi has shown the cognitive capability of Sulawesi inhabitants that might not be possessed by other explorers in Wallacea. In the early half Holocene, the ability shown was to modify the shale tool known as the Toalean techno-complex. However, the view of the development of stone artifact technology in the period between before and early development of the Toalean techno-complex is rarely studied intensively. Leang Batti site is the occupation sites that can fill the information gap through the study of flakes artifact technology. 1376 artifacts were classified and analyzed for flakes by observing morphometric dynamics and tool type technology between the Early to Middle Holocene. The results that in the Early Holocene, the dominant technology was large flakes without modification. In the Middle Holocene, the size of the flakes began to change due to the influence of Toalean with the character of the modified flake technology began to enter in the basic concept of making tools, but not too strong.